Experimental investigation of aeroacoustic damping performance of coupled Helmholtz resonator - Koh, You Jia (2017)
Combustion instabilities can lead to dire and costly consequences to the heat engines if not properly dealt with. Helmholtz resonators are widely used passive acoustic dampers to attenuate acoustic pressure waves arise from instabilities. However, their effectiveness is limited to a narrow frequency bandwidth. This experiment will look into the performance of the perpendicularly-coupled Helmholtz resonator, investigated with three different configurations under cold flow condition in a wind tunnel with wind speed from 0 m/s to 20 m/s.